Decision-making on preservation effort and inventory volume for fresh retailer under strategic consumer behavior - Chuanbo Zhu; Whenyou Zhan (PLoS ONE, 2026)
Based on the theory of rational expectations equilibrium, this study examines the optimal decision-making of fresh retailer under strategic customer behavior. The paper focuses on analyzing the impact of perceived customer value on the retailer’s investment in freshness preservation and configuration in inventory, as well as how market size moderates this influence. The findings reveal that in the face of strategic customer behavior and an increased perception of value for the freshness of products nearing their sell-by date, the retailer tends to lower retail prices, which subsequently affects their enthusiasm for investment in freshness preservation efforts and inventory configuration. The influence of perceived customer value on preservation effort and inventory volume is differential and significantly moderated by market size. When the market size is large, the retailer is inclined to implement optimal preservation measures, but inventory volume may be negatively impacted. With a medium market size, the retailer reduces preservation efforts and inventory levels. However, in situations where perceived customer value is low, the retailer increases inventory volumes. When the market size is small, the impact of strategic customer behavior and perceived customer value on preservation efforts and inventory volumes more pronounced.